2007
DOI: 10.1021/ac0703707
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Behavior of l-Cysteine and Its Detection at Ordered Mesoporous Carbon-Modified Glassy Carbon Electrode

Abstract: In this paper, the electrochemical behavior of L-cysteine (CySH) was investigated thoroughly at an ordered mesoporous carbon-modified glassy carbon (OMC/GC) electrode. The voltammetric studies showed there were three anodic peaks for the electrooxidation of CySH in the pH range of 2.00-5.00; however, one peak disappeared above pH 5.00. This behavior has never been reported before. Through the studies of the effect of pH on the distribution fractions (delta) of the four chemical species of CySH, we conclude onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
176
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(190 citation statements)
references
References 41 publications
9
176
1
3
Order By: Relevance
“…For CySH oxidation at the surface of Au/AuNPs/PNA/ZnSe-QD (Fig. 6 curve d) a possible mechanism may be as follows [26]:…”
Section: ! Cysscy ð8þmentioning
confidence: 99%
See 1 more Smart Citation
“…For CySH oxidation at the surface of Au/AuNPs/PNA/ZnSe-QD (Fig. 6 curve d) a possible mechanism may be as follows [26]:…”
Section: ! Cysscy ð8þmentioning
confidence: 99%
“…Among different methodologies used, electrochemical measurements of thiols have attracted considerable interest because of their high sensitivity, simplicity, low cost and feasibility to the development in vivo sensors and chromatographic detectors [21,22]. Various chemically modified electrodes (CMEs) with electrocatalytic properties have been fabricated and applied in the detection of CySH [23][24][25][26]. The reported CMEs have their advantages and limitations in linear dynamic range, selectivity, sensitivity, detection limit and other characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…This could be the consequence of deprotonation involved in the oxidation process which was facilitated at higher pH values. 25 It was also found that the oxidation peak current of ferulic acid increased sharply with increasing pH from 4.0 to 5.5, and then decreased greatly as pH increasing from 5.5 to 7.0. Thus, the acetate buffer solution at pH 5.5 was chosen as the supporting electrolyte for the determination of ferulic acid.…”
Section: Effect Of Supporting Electrolyte and Phmentioning
confidence: 89%
“…Due to their advantageous characteristics, such as low production costs, wide potential window, high thermal conductivity and mechanical strength, inert electrochemistry [1], carbon materials have been widely used in many technological fields [2,3]. The advantages of carbon materials combined with those of nanostructured materials, such as carbon nanotubes [4,5], carbon nano-fibers [6], highly ordered mesoporous carbons [7,8], etc., have drawn much more attention because of their unusual electronic properties and ability to improve catalytic properties [9]. In solid materials heat is carried by acoustic phonons, which are ion-core vibrations in a crystal lattice, and electrons so that the thermal conductivity coefficient (k) is the sum of the phonon (k p ) and electron (k e ) contributions.…”
Section: Introductionmentioning
confidence: 99%